Can educational videos reduce opioid consumption in trauma inpatients? A cluster-randomized pilot study. Issue 1 (July 2021) - Tseng, Esther S.; Zolin, Samuel J.; Young, Brian T.; Claridge, Jeffrey A.; Conrad-Schnetz, Kristen J.; Curfman, Eric T.; Wise, Nicole L.; Lemaitre, Vetrica C.; Ho, Vanessa P.
Abstract : BACKGROUND: Opioids are often used to treat pain after traumatic injury, but patient education on safe use of opioids is not standard. To address this gap, we created a video-based opioid education program for patients. We hypothesized that video viewing would lead to a decrease in overall opioid use and morphine equivalent doses (MEDs) on their penultimate hospital day. Our secondary aim was to study barriers to video implementation. METHODS: We performed a prospective pragmatic cluster-randomized pilot study of video education for trauma floor patients. One of two equivalent trauma floors was selected as the intervention group; patients were equally likely to be admitted to either floor. Nursing staff were to show videos to English-speaking or Spanish-literate patients within 1 day of floor arrival, excluding patients with Glasgow Coma Scale score less than 15. Opioid use and MEDs taken on the day before discharge were compared. Intention to treat (ITT) (intervention vs. control) and per-protocol groups (video viewers vs. nonviewers) were compared (α = 0.05). Protocol compliance was also assessed. RESULTS: In intention to treat analysis, there was no difference in percent of patients using opioids or MEDs on the day before discharge. In per-protocol analysis, there was no different in percent of patients using opioids on the day before discharge. However, video viewers still on opioids took significantly fewer MEDs than patients who did not see the video (26 vs. 38, p < 0.05). Protocol compliance was poor; only 46% of the intervention group saw the videos. CONCLUSION: Video-based education did not reduce inpatient opioid consumption, although there may be benefits in specific subgroups. Implementation was hindered by staffing and workflow limitations, and staff bias may have limited the effect of randomization. We must continue to establish effective methods to educate patients about safe pain management and translate these into standard practices. LEVEL OF EVIDENCE: Therapeutic, Level IV